2021
DOI: 10.1016/j.artd.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Surgical Helmet and Surgical Hood Application Methods in Reducing Contamination in Arthroplasty Surgery

Abstract: Background: Contamination of the surgeon during gowning is a possible risk factor for prosthetic joint infection in arthroplasty surgery. Surgical helmets are a common form of personal protective equipment used during this type of surgery. Increasingly, there is a focus on the methods of application of the surgical hood and gown while wearing these helmets. Methods: Ultraviolet fluorescent powder was used to represent air-borne contaminant and applied through the airflow inlet of the surgical helmet. Seven met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Kang et al used ultraviolet light and fluorescent powder to assess airborne contamination. 11 They found that early fan activation resulted in contamination of the body and also the scrub nurse. They recommended activation of the helmet after the surgeon was gowned and the gloves were applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kang et al used ultraviolet light and fluorescent powder to assess airborne contamination. 11 They found that early fan activation resulted in contamination of the body and also the scrub nurse. They recommended activation of the helmet after the surgeon was gowned and the gloves were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessed timing of surgical helmet fan activation and concluded that early activation prior to gown dressing increased contamination rates of both the surgeon and scrub nurse. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation